Caracterização de um novo modelo animal para avaliação dos efeitos ansiogênicos de psicoestimulantes - Zanlorenci, Lineane Helena Fernandes [UNIFESP] (2009)
The elevated plus-maze is the most utilized animal model of anxiety nowadays. Unfortunately, it has two important criticisms: 1) it does not evaluate with accuracy the anxiogenic effects of psychostimulants like amphetamine and cocaine and 2) it is sensitive to the phenomenon of one-trial tolerance (OTT). Here, we propose a new animal model to evaluate the anxiogenic effects of psychostimulants. Shortly, the model is based on the enhancement of the locomotor stimulant effects of such drugs (evaluated in an open-field in mice) by a dose of a benzodiazepinic drug which is not able to modify locomotor activity per se. Thus, the locomotor stimulant effect of both amphetamine or cocaine was released by anxiolytic doses (demonstrated by the elevated plus-maze test) of chlordiazepoxide or midazolam. This new model was not vulnerable to the OTT phenomenon since it was also effective in mice previously habituated to the open-field apparatus. Finally, such model was also partially effective in detecting the anxiogenic effect of anxiogenic drugs such as pentilenotetrazole. Indeed, a dose of pentilenotetrazole, which was ineffective in modifying per se mice´s locomotor activity, was effective in decreasing the locomotor stimulant effect of amphetamine (but not of cocaine) in mice.